Gene Expression Profiling in Human Fetal Liver and Identification of Tissue- and Developmental-Stage-Specific Genes through Compiled Expression Profiles and Efficient Cloning of Full-Length cDNAs - Yu, Yongtao; Zhang, Chenggang; Zhou, Gangqiao; Wu, Songfeng; Qu, Xianghu; Wei, Handong; Xing, Guichun; Dong, Chunna; Zhai, Yun; Wan, Jinghong; Ouyang, Shuguang; Li, Li; et al.

(untitled) (Genome Research, 2001)
Fetal liver intriguingly consists of hepatic parenchymal cells and hematopoietic stem/progenitor cells. Human fetal liver aged 22 wk of gestation (HFL22w) corresponds to the turning point between immigration and emigration of the hematopoietic system. To gain further molecular insight into its developmental and functional characteristics, HFL22w was studied by generating expressed sequence tags (ESTs) and by analyzing the compiled expression profiles of liver at different developmental stages. A total of 13,077 ESTs were sequenced from a 3′-directed cDNA library of HFL22w, and classified as follows: 5819 (44.5%) matched to known genes; 5460 (41.8%) exhibited no significant homology to known genes; and the remaining 1798 (13.7%) were genomic sequences of unknown function, mitochondrial genomic sequences, or repetitive sequences. Integration of ESTs of known human genes generated a profile including 1660 genes that could be divided into 15 gene categories according to their functions. Genes related to general housekeeping, ESTs associated with hematopoiesis, and liver-specific genes were highly expressed. Genes for signal transduction and those associated with diseases, abnormalities, or transcription regulation were also noticeably active. By comparing the expression profiles, we identified six gene groups that were associated with different developmental stages of human fetal liver, tumorigenesis, different physiological functions of Itoh cells against the other types of hepatic cells, and fetal hematopoiesis. The gene expression profile therefore reflected the unique functional characteristics of HFL22w remarkably. Meanwhile, 110 full-length cDNAs of novel genes were cloned and sequenced. These novel genes might contribute to our understanding of the unique functional characteristics of the human fetal liver at 22 wk.[The sequence data described in this paper have been submitted to the GenBank data library under the accession nos. listed in Table 6 herein]